2017
DOI: 10.1177/2381468317714474
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Educational and Behavioral Interventions to Level of Health Literacy: A Systematic Review

Abstract: Background: The relative value of universal compared to contingent approaches to communication and behavioral interventions for persons of low health literacy remains unknown. Objective: To examine the effectiveness of interventions that are tailored to individual health literacy level compared to nontailored interventions on health-related outcomes. Design: Systematic review. Data Sources: PubMed and Embase databases. Eligibility Criteria: Studies were eligible if they were in English, used an experimental or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
0
31
1
2
Order By: Relevance
“…Although disease knowledge alone does not ensure required behavior modifications, the assessment of patients’ disease knowledge is a cornerstone is designing tailored health educational intervention 11,12. Diabetes education, with consequent improvements in patients’ knowledge about disease and self-care activities, results in achieving optimal glycemic control and reduction in disease-related complications 8,13…”
Section: Introductionmentioning
confidence: 99%
“…Although disease knowledge alone does not ensure required behavior modifications, the assessment of patients’ disease knowledge is a cornerstone is designing tailored health educational intervention 11,12. Diabetes education, with consequent improvements in patients’ knowledge about disease and self-care activities, results in achieving optimal glycemic control and reduction in disease-related complications 8,13…”
Section: Introductionmentioning
confidence: 99%
“…This may improve participation in the training and expected outcomes. Previous studies have also indicated positive effects of tailoring education programmes according to the needs and contexts of learners [25][26][27].…”
Section: Discussionmentioning
confidence: 98%
“…Individualized and tailored patient education may be an effective strategy to improve knowledge and disease control indicators. [ 35 ] In a study of renal transplant recipients' experiences of participating in a new, tailored, evidence-based education program, it was found that they feel more satisfied with receiving individualized education. [ 36 ] On the other hand, participants stated that facilitating the processes using new technologies, teamwork education, and patient and family accessibility is necessary to achieve PFCE.…”
Section: Discussionmentioning
confidence: 99%